Expression of connexin43 in oral submucous fibrosis, oral epithelial dysplasia and oral squamous cell carcinoma: A cross-sectional immunohistochemical study - Raghavelu Narendran Mugundan; Uma Devi Krishna Mohan Rao; Rooban Thavarajah; Elizabeth Joshua; Kannan Ranganathan (Wolters Kluwer Medknow Publications, 2023)
Introduction: Connexins are specialized gap junction (GJ) proteins that are necessary for the maintenance of cellular homeostasis. The loss of GJ leads to the loss of cellular cohesion, promoting tumor progression. Not much is known about the role of connexin43 (Cx43) in oral submucous fibrosis (OSF), oral epithelial dysplasia (OED), and in OSF that had transformed into oral squamous cell carcinoma (OSCC). Materials and methods: A total of 39 tissue samples was grouped into group I: Normal oral mucosa (NC) (n = 6), group II: OSF (n = 14), group III: OED (n = 12), and group IV: OSCC with a history of OSF (n = 7). Sections were stained with Cx43 antibody and analyzed for staining intensity in the basal, suprabasal cell layers, and connective tissue. The Chi-square test was used to assess significant association and Kappa statistics between the variable and interobserver variability. Results: Cx43 exhibited varying levels of expression in the cell membrane of suprabasal cell layer across all the groups. The difference in expression was statistically significant (P = 0.033). In OSF, there was a moderate presence of Cx43, whereas NC, dysplasia, and OSCC with OSF showed no detectable Cx43 expression. Notably, OSF displayed higher Cx43 expression compared to OED. Conversely, OSCC with OSF demonstrated reduced expression of Cx43 in epithelial tumor islands that had invaded the connective tissue (P = 0.033). Conclusion: Cx43 expression was significantly decreased as there was a progression in OED severity and reduced in OSCC with a history of OSF.